A Class of Harmonic Multivalent Functions for Higher Derivatives Associated with General Linear Operator - Delphi, Ali Musaddak; Jassim, Kassim A. (Iraqi Journal of Science, 2022)
The main goal of this paper is to introduce the higher derivatives multivalent harmonic function class, which is defined by the general linear operator. As a result, geometric properties such as coefficient estimation, convex combination, extreme point, distortion theorem and convolution property are obtained. Finally, we show that this class is invariant under the Bernandi-Libera-Livingston integral for harmonic functions.